QUALITY ASSURANCE SYSTEM POLICY IN EDUCATION: A COMPARATIVE STUDY BETWEEN INDONESIA AND FINLAND - Ali, Andi Ibrahim; Hermansyah, Eka (Jurnal Penelitian Kebijakan Pendidikan, 2024)
This study aims to compare quality assurance policies in education between Indonesia and Finland, offering valuable insights for future policy development as the Indonesian education system undergoes transformation. The methodology used involved qualitative case studies that examined government documents, journals, reports, and online news to compare the quality assurance policies in a tabular format. This research focused solely on comparing the scope of quality assurance policies, without examining their implementation. The results revealed some similarities between Indonesia and Finland, particularly regarding teacher qualifications and the curriculum. However, there were significant differences between the two countries. For instance, Finland strongly emphasizes early childhood education to prepare students as lifelong learners. In contrast, Indonesia has traditionally focused more on basic and secondary education, though it is beginning to recognize the importance of early childhood education. Hence, Indonesia could learn from Finland by strengthening its early childhood education, making teachers’ appointments more competitive, and decentralizing the supervision of education quality from the central government to local authorities.